2012
DOI: 10.1177/0022042612467009
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward and Sexual Partnerships With Drug Dealers Among Young Adult African American Females in Socially Disorganized Communities

Abstract: Drug markets in disadvantaged African American neighborhoods have altered social and sexual norms as well as sexual networks, which impact an individual’s risk of contracting a sexually transmitted infection. Presently, we describe the prevalence of sexual partnerships with males involved with illegal drugs among a sample of non-drug-dependent females. In 2010, 120 Black females aged 18 to 30 years completed a semistructured HIV-risk interview. Descriptive statistics revealed approximately 80% of females perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Likewise, drug trafficking was listed by the majority of African Americans in this study as a reason for the lack of eligible same-race partners. Other research has demonstrated that drug market activity is rampant in many economically disadvantaged African American communities and related to STI risk (Adimora & Schoenbach, 2005; Floyd & Brown, 2012). Specifically, Floyd & Brown (2012) report that African American women in disadvantaged neighborhoods frequently have relationships with men involved in drug trafficking and who have substantial links to higher-risk drug and prison populations; and, this is a contributing contextual factor to STI transmission.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Likewise, drug trafficking was listed by the majority of African Americans in this study as a reason for the lack of eligible same-race partners. Other research has demonstrated that drug market activity is rampant in many economically disadvantaged African American communities and related to STI risk (Adimora & Schoenbach, 2005; Floyd & Brown, 2012). Specifically, Floyd & Brown (2012) report that African American women in disadvantaged neighborhoods frequently have relationships with men involved in drug trafficking and who have substantial links to higher-risk drug and prison populations; and, this is a contributing contextual factor to STI transmission.…”
Section: Discussionmentioning
confidence: 99%
“…Additional longitudinal research is needed to further examine partner characteristics and STI transmission, as well as the role that drug use plays in this relationship. In particular, studies which examine African American women’s social networks over time – including alter characteristics in both their drug and sexual networks – are warranted when examining disease transmission (Floyd & Brown, 2012; Flom et al, 2001). Social network approaches have great utility when examining racial disparities in STIs as African American’s sexual networks are more racially homophilous and have a higher prevalence of concurrent sexual partnerships (Adimora et al, 2002; Adimora & Schoenbach, 2005; Laumann & Youm, 1999).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…30,31 Alcohol outlets and drug markets provide venues where unstable and short-term relationships with risky partners may be formed. 32,33 . Violence and markedly elevated male incarceration rates, which have been associated with alcohol outlet density, drug markets, and low male to female sex ratios among African Americans 34,35 may influence relationship “churning” by determining partner availability and establishing norms around partner selection.…”
Section: Introductionmentioning
confidence: 99%